ANTIMUTAGENIC ACTIVITY OF SYZYGIUM AROMATICUM EXTRACT IN MICE USING BONE MARROW MICRONUCLEUS TEST - BHANU PRIYA. K,; VENKATA S KOTAKADI,; JOSTHNA. P, (International Journal of Pharma and Bio Sciences, 2013)
Syzygium aromaticum is commonly known as clove, it is the dried bud of the tree. Cloves are of high medicinal value they are widely used in ayurveda, chinese medicine, western herbalism and also as a food ingredient. The present study was taken up to evaluate antimutagenic activity of ethyl acetate extract of clove with reference to the frequency of polychromatic erythrocytes (PCE) in the bone marrow of mice, administered intraperitoneally (i.p) using bone marrow micro nucleus test. Mice were given with ethyl acetate extract doses of 500,750 mg/kg/day intraperitoneal. In addition, Mitomycin C (MMC) given to the animals at the dose of 4mg/kg by single intraperitoneal injection. Smear specimens were prepared from bone marrows and stained with May-Grunwald’s followed by Giemsa stain then the frequencies of micro nucleated PCEs and the ratio of total number of (PCE/NCE) were calculated. Ethyl acetate extract of Syzygium aromaticum (750mg/kg) showed significant antimutagenic activity.